Antioxidant Properties of Natural Products: A Themed Issue in Honor of Professor Isabel C.F.R. Ferreira A Themed Issue in Honor of Professor Isabel C.F.R. Ferreira - Barros, Lillian (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
It would be almost impossible to discuss natural products without mentioning the extensive knowledge that Professor Isabel C.F.R. Ferreira has contributed to this field. She has been an instrumental scientist in the development and dissemination of information about these products; throughout her career as a researcher, she explored more than 300 food matrices, including plants and mushrooms, as possible sources of these natural compounds. In her studies, the determination of the bioactive properties of the developed extracts and identified molecules from natural matrices stand out.Antioxidant properties are essential to break the oxidation chain that can occur in an organism, for example, in the human body, or on a substrate, such as in food. In organisms, the oxidative process may be responsible for the generation of free radicals that attack cells, which leads to the development of serious diseases, such as cardiovascular and neurological disorders. The intake of compounds with antioxidant capacities can provide beneficial health effects. In food, oxidation can lead to the loss of product quality due to the deterioration of chemical, physical, and sensory characteristics. Natural products with antioxidant activity can add value to food products due to their functional properties and health benefits.Given the importance of minimizing oxidative processes, several authors have been looking for new compounds with antioxidant activity. In this context, plants, mushrooms, and marine and bee products, among others, may have several classes of compounds in their chemical composition that exert this bioactivity, such as vitamins, polyphenols, organic acids, and pigments. In this Special Issue, Antioxidants Properties of Natural Products: A Themed Issue in Honor of Professor Isabel C.F.R. Ferreira, 23 selected studies explore different food matrices as sources of bioactive molecules with potential use as natural products with several functionalities, including antioxidants properties.